2020
DOI: 10.2337/dc20-1234/suppl.12077391.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adolescent Obesity and Early-onset Type 2 Diabetes

Abstract: <b>OBJECTIVE</b>: Type 2 diabetes (T2D) is increasingly diagnosed at younger ages. We investigated the association of adolescent obesity with incident T2D at early adulthood. <p><b>RESEARCH DESIGN AND METHODS</b>: A nationwide, population-based study of 1,462,362 adolescents (59% men; mean age 17.4 years) evaluated during 1996-2016. Data were linked to the Israeli National Diabetes Registry. Weight and height were measured at study entry. Cox proportional models were applied. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…It was reported that obesity was a more general feature of early-onset type 2 diabetes than it is in later-onset type 2 diabetes ( 3 , 36 ). A prospective study including 1,462,362 adolescents confirmed that severe obesity significantly increased the risk for incidence of type 2 diabetes in young ( 20 ). Importantly, we found that the association of age at diagnosis of diabetes with risk of CVD was more pronounced among patients with obesity or overweight than those with normal weight.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It was reported that obesity was a more general feature of early-onset type 2 diabetes than it is in later-onset type 2 diabetes ( 3 , 36 ). A prospective study including 1,462,362 adolescents confirmed that severe obesity significantly increased the risk for incidence of type 2 diabetes in young ( 20 ). Importantly, we found that the association of age at diagnosis of diabetes with risk of CVD was more pronounced among patients with obesity or overweight than those with normal weight.…”
Section: Discussionmentioning
confidence: 92%
“…During the past decades, China has experienced a rapid transition to western lifestyles with more sedentary behavior and a high energy/fat diet ( 19 ), leading to the escalating rates of obesity and related metabolic diseases, including type 2 diabetes. The rise in the prevalence of obesity in early and middle-aged population is likely to increase the incidence of early-onset type 2 diabetes ( 20 ). Previous studies have reported a strong relationship between obesity in youth and subsequent onset of type 2 diabetes ( 20 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes a detailed interview, review of medical history and a physical examination. Measurement of weight, height, and systolic and diastolic blood pressure were performed for most of the adolescents (98.5%) as described elsewhere [17,18]. Mean arterial pressure was calculated: ðSystolic BP þ 2 Ã Dias tolic BPÞ 3 .…”
Section: Covariatesmentioning
confidence: 99%
“…Residential SES was based on locality of residence at the time of examination and was determined according to a 1-to-10 ordinal scale reflecting SES characteristics of residential areas, as defined by the Israeli Bureau of Statistics [19]. Adolescents were classified into three categories of residential SES: low (1À4), intermediate (5À7), and high (8À10) as reported previously [17]. Data on years of attained education were received from the Israeli Ministry of Education and dichotomized as previously described using a cutoff of 11 years of formal schooling (Supplementary Appendix) [17].…”
Section: Covariatesmentioning
confidence: 99%